Modernisasi Pendidikan Melalui Desentralisasi: Studi Literatur Tentang Peran Pemerintah Daerah Dalam Pembangunan Pendidikan - Pratiwi, Utari; F, Firman; N, Nurfarhanah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Educational decentralization is a key strategy in the modernization of Indonesia’s education system, granting greater authority to local governments to manage and develop education based on regional needs. This study aims to examine the strategic role of local governments in educational development through decentralization policies, as well as the challenges faced in their implementation. The findings indicate that decentralization contributes to improving the quality, relevance, and equity of educational access through localized curriculum adaptation, the implementation of school-based management, and teacher training tailored to local contexts. Local governments also play a crucial role in resource management, budget allocation, and the development of educational infrastructure. However, challenges such as disparities in educational quality among regions, limited professional human resources, and bureaucratic obstacles remain to be addressed. This study emphasizes that the success of educational decentralization depends heavily on the synergy between central and local governments, strong legal frameworks, and active community participation. Therefore, decentralization can serve as a driving force in establishing an inclusive, adaptive, and globally competitive education system.